A review on treatment of membrane concentrates generated from landfill leachate treatment processes - Keyikoğlu, Ramazan; Karatas, Okan; Rezania, Hamidreza; Kobya, Mehmet; Vatanpour, Vahid; Khataee, Alireza (Elsevier, 2021)
Landfill leachate (LL) is highly toxic wastewater and comprises various pollutants such as organic compounds, biological organisms, xenobiotics, heavy metals, inorganic salts, and ammonia. The integration of conventional methods with membrane processes has become indispensable due to the enforcement of stricter regulations for the LL discharge. The integrated membrane technologies achieve a pollutant removal efficiency of higher than 95% with a large volume of treated leachate and a low capital cost investment. However, the drawback of these processes is the production of a membrane concentrate with even more hazardous characteristics. This review presents the state of the art methods along with the recent improvements to the existing processes for the treatment of membrane concentrates. The techniques are mainly divided into two categories of conventional, advanced methods and the hybridization of them. The operating conditions, performances of the individual processes along with wastewater characteristics were summarized in detail. Generally, the leachate concentrate properties such as salinity, COD, BOD5/COD ratio, and toxicity are essential parameters for the selection of appropriate treatment methods. It was found that single treatment processes are not able to reach desirable membrane concentrate treatment and need an engineered combination of these techniques to achieve satisfactory removal efficiencies.
Keywords: Advanced oxidation processes; Electrochemical treatment processes; Fenton based processes; Landfill leachate; Membrane concentrate